Evaluation of the Degree of Non-Linear Exchange Rate Pass-Through in Different Consumption Groups in Iran - Mahdi Aminirad; Sima Shaygan Mehr (International Journal of Management, Accounting and Economics)
The effect of exchange rate changes on prices is one of the controversial economic issues that has attracted the attention of policymakers and academics. Knowing about the exchange rate Pass-through (ERPT) and its reaction to different inflation environments helps economic policy makers to adopt appropriate exchange policies. In this paper, the effect of exchange rate changes on consumer price index groups (CPI & 12 COICOP categories) has been analyzed using the threshold vector autoregression (TAR) model in Iran. For this purpose, quarterly data for the period 2000Q2-2023Q3 have been used. In this research, the inflation rate of the previous quarter is considered a threshold variable, and two inflation regimes (high and low) are determined based on it. According to the results, although the ERPT for CPI is larger in the high inflation regime than in the low inflation regime in Iran; however, significant differences can be seen between the two inflation regimes in the 12 COICOP categories. In the low inflation regime, the ERPT among COICOP categories varies between 0.138 to 0.783. In the high inflation regime, the ERPT among COICOP categories varies between 0.217 and 0.854.